Spiritualitas Ebamukai dalam Terang Ensiklik Fratelli Tutti Art 87-127 dalam Rangka Memuliakan Martabat Manusia - Yohanes Kayame (JURNAL PASTORAL KATEKETIK, 2024)
The purpose of this study is to discuss the spirituality of ebamukai in the light of the Encyclical Fratelli Tutti art 87-127 in order to glorify human dignity. The author would like to bring up the values contained in ebamukai as an expression of glorifying human dignity. This research uses qualitative research methods by analyzing books, journals or online news that discuss the topic to be discussed. In addition, the author conducts in-depth interviews with figures who are considered familiar with the topic to be discussed. All data obtained will be sorted and analyzed descriptively. This research found that ebamukai is a practice that is full of life values that can be used to ennoble human dignity. These values include love, solidarity, compassion, open-heartedness and giving or sharing. All of these values are spearheaded by God as the One of Love and who unites all people. So ebamukai is not just an activity to collect money but a meaningful activity in glorifying human dignity and is sacred.